2023
DOI: 10.1172/jci.insight.170671
|View full text |Cite
|
Sign up to set email alerts
|

The glucagon-like peptide-1 (GLP-1) analogue semaglutide reduces alcohol drinking and modulates central GABA neurotransmission

Vicky Chuong,
Mehdi Farokhnia,
Sophia Khom
et al.

Abstract: Growing evidence indicates that the glucagon-like peptide-1 (GLP-1) system is involved in the neurobiology of addictive behaviors, and GLP-1 analogues may be used for the treatment of alcohol use disorder (AUD). Here, we examined the effects of semaglutide, a long-acting GLP-1 analogue, on biobehavioral correlates of alcohol use in rodents. A drinking-in-the-dark procedure was used to test the effects of semaglutide on binge-like drinking in male and female mice. We also tested the effects of semaglutide on bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 126 publications
2
15
2
Order By: Relevance
“…This is in contrast to Chuong et al (2023), which observed a significant increase in both the frequency and amplitude of sIPSCs after CIE exposure. Although seemingly in at least partial agreement with the current findings, Chuong et al (2023) performed recordings within an hour after the final ethanol vapor exposure session and allowed slices containing the IL mPFC to undergo acute withdrawal in vitro . In addition, neither study distinguished between distinct cortico-subcortical projections, making comparisons between the current findings and these studies difficult.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to Chuong et al (2023), which observed a significant increase in both the frequency and amplitude of sIPSCs after CIE exposure. Although seemingly in at least partial agreement with the current findings, Chuong et al (2023) performed recordings within an hour after the final ethanol vapor exposure session and allowed slices containing the IL mPFC to undergo acute withdrawal in vitro . In addition, neither study distinguished between distinct cortico-subcortical projections, making comparisons between the current findings and these studies difficult.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, heightened impulsivity (Irimia et al, 2014; Starski et al, 2020; Walker et al, 2011), deficits in behavioral flexibility (Badanich et al, 2011; Hu et al, 2015; Mejia-Toiber et al, 2014; Trantham-Davidson et al, 2014; Varodayan et al, 2018), impairments in fear extinction and retrieval (Holmes et al, 2012), and increased anxiety-like behavior (Hughes et al, 2021; Mejia-Toiber et al, 2014; Pleil et al, 2015; Starski et al, 2020; Varodayan et al, 2018) have been observed in rodents exposed to chronic ethanol. In some studies, these deficits are associated with physiological neuroadaptations in prelimbic (PL) (Holmes et al, 2012; Hughes et al, 2021; Kroener et al, 2012; Pleil et al, 2015) and infralimbic (IL) (Chuong et al, 2023; Flores-Ramirez et al, 2023; Pleil et al, 2015; Varodayan et al, 2018) subregions of the mPFC. Of note, while few studies report data from both mPFC subregions in the same experiment, those that do have found that PL and IL are differentially affected by chronic ethanol exposure (Pleil et al, 2015; Varodayan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the effects were not specific to alcohol, as semaglutide also reduced the intake of various non-alcoholic solutions, suggesting a broader role in suppressing behaviors related to appetite, thirst, and palatability. The research suggested that semaglutide influenced GABAergic synaptic transmission in brain areas associated with alcohol-related behaviors [ 101 ].…”
Section: Resultsmentioning
confidence: 99%
“…Its dysregulation may lead to anhedonia and other depressive symptoms. [ 17 ] In fact, studies have shown reduced cravings for addictive substances after using GLP-1RAs, [ 18 ] possibly related to their effect on the dopamine reward system. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%